Assessing the Effectiveness of Shared Decision-Making in Enhancing Medication Adherence among Chronic Disease Patients in Primary Healthcare - A Systematic Literature Review - Salakay, Elisa Nugraha Haryadi; Hau Mahu, Grace Fitriana Primasari; Rahayu, Agnes Supraptiwi (Faculty of Medicine, Public Health, and Nursing, 2023)
Objective. This study investigated the effect of shared decision-making (SDM) approaches on medication adherence among individuals with chronic diseases receiving primary healthcare from studies conducted between 2012 and 2023. Method. A literature review was conducted in PubMed, Scopus, ProQuest, and EBSCO databases, resulting in 220 articles. Only randomized controlled trials (RCTs) were included; the two studies that matched the inclusion criteria were examined. Results. Two RCTs in primary healthcare settings examined SDM interventions. The study on hypertension patients found no significant effect of SDM training on medication adherence, while the study on depression patients using a decision aid also found no significant impact on medication adherence. Discussion & Conclusion. SDM interventions did not significantly improve medication adherence in chronic diseases such as hypertension and depression. Factors identified include short training duration, the complexity of Adherence, and a need for consistent evidence. The conclusion suggests that SDM may not significantly affect chronic disease patients receiving primary healthcare medication adherence. However, given the limited number of eligible studies, more research is needed in diverse settings and populations.